2012
DOI: 10.2174/092986712799462559
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and Multiple Sclerosis

Abstract: Multiple sclerosis (MS) has been considered for a long time a typical inflammatory demyelinating disease of the central nervous system due to autoimmunity targeting oligodendrocytes with sparing of axons until advanced stages of the disease. For this reason, most of the earliest experimental studies focused on the role of cytokines and chemokines at the site of oligodendrocytes loss and on the importance in MS pathogenesis of classical inflammatory mechanisms. As a result, several attempts to treat MS through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In our research, mir-26a-5p, showed a significant change in the level of expression, based on the INF-βresponse, at the different stages of treatment in INF-β treated responder RRMS (Figure 2). Studies have demonstrated that glutamatergic regulation can take place in MS symptoms and treatment [27]. Under pathological conditions an excess of glutamate in the synaptic space can trigger a toxic cascade leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, mir-26a-5p, showed a significant change in the level of expression, based on the INF-βresponse, at the different stages of treatment in INF-β treated responder RRMS (Figure 2). Studies have demonstrated that glutamatergic regulation can take place in MS symptoms and treatment [27]. Under pathological conditions an excess of glutamate in the synaptic space can trigger a toxic cascade leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation might be the primary cause of neurodegeneration occurring independent of oligodendrocyte damage, as neuronal loss can be observed in normalappearing white matter in MS patients (Evangelou et al, 2000). This inflammation-induced neurodegeneration might be due to disruptions of glutamate release and clearance that are documented in MS tissue (reviewed by Frigo et al, 2012;Tilleux and Hermans, 2007). Glutamate concentrations are significantly increased in the cerebrospinal fluid, in acute brain lesions and in normal appearing white matter of MS patients (Srinivasan et al, 2005;Stover et al, 1997).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Additional possible strategies for preventing ROS formation from glutamate sources is the inhibition of the NMDA receptor with a selective antagonist and the chelation of calcium ions [119], as well as inhibition of the enzyme glutamate carboxypeptidase II [120,121]. Moreover, evidence is now increasing that excessive glutamate is released at the site of demyelination and axonal degeneration in multiple sclerosis plaques [122], thus raising the possibility that the modulation of glutamate release and transport, as well as a receptors blockade, might be relevant targets for the development of future neurodegenerative disease therapeutic interventions.…”
Section: Glutamate As a Source Of Rosmentioning
confidence: 99%